Microwave photonics promotes emerging integrated sensing and communication technology - Wenlin Bai; Xihua Zou; Jiaxin Xu; Aiping Xie; Zhiyu Chen; Xin Zhong; Ningyuan Zhong; Fengwei Liu; Bowen Zhang; Tao Zhou (APL Photonics)
Integrated sensing and communication (ISAC), a key technology for next-generation wireless networks (e.g., 5G-A and 6G), aims to provide both large-capacity wireless communication and high-resolution microwave sensing/ranging simultaneously. Microwave photonics (MWP)-ISAC, with its unique features such as high frequency, large bandwidth, low frequency-dependent loss, flat frequency response, fast analog signal processing, and strong immunity to electromagnetic interference, offers superior performance in terms of data rate and range/imaging resolution compared to traditional electronic technologies. This paper presents a comprehensive overview of the latest advancements in MWP-ISAC techniques, covering multi-domain resource multiplexing (MDRM) and integrated waveform (IW) strategies. We review four MDRM methods: time division multiplexing, frequency division multiplexing, space division multiplexing, and hybrid resource division multiplexing. In addition, we discuss sensing-centric IWs (including phase modulated continuous-wave and linear frequency modulation-based parameter modulation) and communication-centric IWs (such as orthogonal frequency division multiplexing and orthogonal chirp division multiplexing).